Behavioral, neurochemical and pharmaco-EEG profiles of the psychedelic drug 4-bromo-2,5-dimethoxyphenethylamine (2C-B) in rats - Páleníček, Tomáš; Fujáková, Michaela; Brunovský, Martin; Horáček, Jiří; Gorman, Ingmar; Balíková, Marie; Rambousek, Lukáš; Syslová, Kamila; Kačer, Petr; Zach, Petr; Bubeníková-Valešová, Věra; Tylš, Filip; et al. (Psychopharmacology, 2013)
RATIONALE AND OBJECTIVES: Behavioral, neurochemical and pharmaco-EEG profiles of a new synthetic drug 4-bromo-2,5-dimethoxyphenethylamine (2C-B) in rats were examined. MATERIALS AND METHODS: Locomotor effects, prepulse inhibition (PPI) of acoustic startle reaction (ASR), dopamine and its metabolite levels in nucleus accumbens (NAc), EEG power spectra and coherence in freely moving rats were analysed. Amphetamine was used as a reference compound. RESULTS: 2C-B had a biphasic effect on locomotion with initial inhibitory followed by excitatory effect; amphetamine induced only hyperlocomotion. Both drugs induced deficits in the PPI; however they had opposite effects on ASR. 2C-B increased dopamine but decreased 3,4-dihydroxyphenylacetic acid (DOPAC) in the NAc. Low doses of 2C-B induced a decrease in EEG power spectra and coherence. On the contrary, high dose of 2C-B 50 mg/kg had a temporally biphasic effect with an initial decrease followed by an increase in EEG power; decrease as well as increase in EEG coherence was observed. Amphetamine mainly induced an increase in EEG power and coherence in theta and alpha bands. Increases in the theta and alpha power and coherence in 2C-B and amphetamine were temporally linked to an increase in locomotor activity and DA levels in NAc. CONCLUSIONS: 2C-B is a centrally active compound similar to other hallucinogens, entactogens and stimulants. Increased dopamine and decreased DOPAC in the NAc may reflect its psychotomimetic and addictive potential and monoaminoxidase inhibition. Alterations in brain functional connectivity reflected the behavioral and neurochemical changes produced by the drug; a correlation between EEG changes and locomotor behavior was observed.
Keywords: pohybová aktivita; dopamin; chování zvířat; halucinogeny; nucleus accumbens; kyselina 3,4-dihydroxyfenyloctová; Dose-Response Relationship, Drug; Reflex, Startle; krysa rodu Rattus; dimethoxyfenylethylamin; Hallucinogens; elektroencefalografie; zvířata; 3,4-Dihydroxyphenylacetic Acid; Amphetamine; potkani Wistar; úleková reakce; Rats, Wistar; amfetamin; Male; Dopamine; Electroencephalography; Rats; vztah mezi dávkou a účinkem léčiva; Motor Activity; Animals; Dimethoxyphenylethylamine; mužské pohlaví; Behavior, Animal; Nucleus Accumbens